SrCe0.95Y0.05O3-δ-ZnO dual-phase membranes for hydrogen permeation - Wang, T.; Zhang, H.; Meng, B.; Wang, X.; Sunarso, J.; Tan, X.; Liu, Shaomin (Royal Society of Chemistry, 2016)
A hydrogen permeation membrane plays a key role in membrane reactor applications for hydrogen production. To this end, a SrCe0.95Y0.05O3-δ (SCY) proton conductor has been regarded as an attractive candidate. This work aimed to increase the practical value of SCY by making its composite with ZnO. The presence of ZnO was found to increase the sinterability of SCY, resulting in a 200 °C reduction in the sintering temperature required to obtain a dense membrane as normally achieved at 1400 °C. The electrical conductivities of the composites in a hydrogen atmosphere were also enhanced by the addition of ZnO. The fact that the sintering of the composite membrane at 1200 °C leads to the formation of a dense composite body while not resulting in the formation of new phases detectable by powder X-ray diffractions highlights the chemical compatibility of SCY and ZnO. The phase stability of the composite to water was also improved relative to the pure SCY. Hydrogen permeation fluxes were increased with the ZnO content until 20% (by weight) over which, the flux degradation started to occur, most probably due to the ZnO reduction by hydrogen. As such, SCY-10% ZnO is deemed as the optimized composite. The maximum flux attained using this membrane was 0.039 mL (STP) cm-2 min-1 at 900 °C. Long term evaluation testing for over a 48 hour-period was performed where the SCY-10% ZnO membrane was subjected to alternating cycles of CO2 and N2 sweep gas flows. Despite the significant overall degradation in performance beyond the 3rd cycle, the results show substantial recovery in the performance over the 2nd and 3rd cycles. In contrast with these conventional perovskite and metal dual phase membranes, this work features an attractive concept to develop a proton conducting membrane from SCY-based composite membranes.